A dynamic Ellsberg urn experiment - Dominiak, Adam; Dürsch, Peter; Lefort, Jean-Philippe (Discussion paper series, 2009)
Two rationality arguments are used to justify the link between conditional and unconditional preferences in decision theory: dynamic consistency and consequentialism. Dynamic consistency requires that ex ante contingent choices are respected by updated preferences. Consequentialism states that only those outcomes which are still possible can matter for updated preferences. We test the descriptive validity of these rationality arguments with a dynamic version of Ellsberg's three color experiment and find that subjects act more often in line with consequentialism than with dynamic consistency.
Online publiziert: 2009
Keywords: Graue Literatur